The Relationship between Hip Ultrasound Result and the Diagnosis of Developmental Dysplasia of the Hip in Premature Infants - Osman, Ahmed; Conroy, Sara; Slaughter, Jonathan L. (American Journal of Perinatology, 2025)
The study objective was to evaluate the relationship between the first hip ultrasound (HUS) result and developmental dysplasia of the hip (DDH) diagnosis in preterm infants. Additionally, we report the types of treatment for preterm infants diagnosed with DDH.This is a retrospective chart review of infants born between January 1, 2009, and December 31, 2018, at <37 weeks of gestation who had HUS in the first year of life. Positive predictive value (PPV), negative predictive value (NPV), sensitivity, and specificity for abnormal and normal HUS results were calculated.From 2,397 infants analyzed, 71 (3%) infants were diagnosed with DDH. The majority (n = 2,140; 89%) of patients had normal HUS, with only 5 (0.2%) infants later diagnosed with DDH. The sensitivity of HUS was 0.91 PPV 0.8, the specificity was 0.99 and NPV was 0.99. Of the 196 (8%) infants with equivocal results, 17 (9%) had subsequent DDH diagnoses.For infants diagnosed with DDH, the majority (n = 41; 58%) were treated nonoperatively with Pavlik harness. Surgical correction was performed in 26 (36%) patients.A normal first HUS result in preterm infants has an excellent NPV for the diagnosis of DDH. Abnormal first HUS has a good PPV. Those with an equivocal result may need close follow-up.
Keywords: prematurity; developmental dysplasia of the hip; hip ultrasound; Pavlik harness